2018
DOI: 10.1038/s41467-018-04194-9
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 is a mechanically activated ion channel and mediates pressure induced pancreatitis

Abstract: Merely touching the pancreas can lead to premature zymogen activation and pancreatitis but the mechanism is not completely understood. Here we demonstrate that pancreatic acinar cells express the mechanoreceptor Piezo1 and application of pressure within the gland produces pancreatitis. To determine if this effect is through Piezo1 activation, we induce pancreatitis by intrapancreatic duct instillation of the Piezo1 agonist Yoda1. Pancreatitis induced by pressure within the gland is prevented by a Piezo1 antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
141
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 58 publications
6
141
0
Order By: Relevance
“…In non-neuronal tissue, PIEZO1 has been shown to regulate numerous physiological processes ranging from the maintenance of epithelial barrier integrity (24,26) to lymphatic valve development (27), red blood cell volume (28) and myotube formation (29). In the pancreas, PIEZO1 mediates pressure-induced pancreatitis (30), however, roles for PIEZO1 channels in other exocrine organs, including the mammary gland, remain unexplored. Here, we characterize the mammary force landscape and investigate roles for PIEZO1 channels in sensing and transducing epithelial cell forces to sustain or suspend lactation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-neuronal tissue, PIEZO1 has been shown to regulate numerous physiological processes ranging from the maintenance of epithelial barrier integrity (24,26) to lymphatic valve development (27), red blood cell volume (28) and myotube formation (29). In the pancreas, PIEZO1 mediates pressure-induced pancreatitis (30), however, roles for PIEZO1 channels in other exocrine organs, including the mammary gland, remain unexplored. Here, we characterize the mammary force landscape and investigate roles for PIEZO1 channels in sensing and transducing epithelial cell forces to sustain or suspend lactation.…”
Section: Introductionmentioning
confidence: 99%
“…(60). All samples were obtained with informed consent and patients (female, aged[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] were recruited under a protocol approved by the Indiana University Institutional Review Board (IRB protocol number 1011003097) and according to The Code of Ethics of the World Medical Association (Declaration of Helsinki). The current project received additional, site-specific approval from the Mater Misericordiae Ltd Human Research Ethics Committee.…”
mentioning
confidence: 99%
“…A prior report has suggested lack of specificity of Yoda1 for Piezo1 channels 40 but the GsMTx4 toxin used as the basis of this proposal has limited value as a tool for evaluating Piezo1. Other prior studies have shown that genetic deletion of Piezo1 abolishes Yoda1's effects 10,36,41,42 and that Piezo1 knockdown by RNA interference suppresses its effects 14,30,[43][44][45][46] , consistent with Yoda1 having only Piezo1-mediated effects. Specific structure-activity requirements of Yoda1 at Piezo1 have been observed 24 and it does not activate Piezo2 21 .…”
Section: Discussionmentioning
confidence: 52%
“…During forskolin stimulation the secreted fluid expands the lumen and the increasing intraluminal pressure prevents water efflux that might therefore not follow the ion current linearly. In addition, the increased tension might activate the mechanoreceptors (such as Piezo1) in the apical membrane of epithelial cells [40]. This shall not be a problem in samples with CFTR expression defects, where the initial fluid secretion is marginal [41].…”
Section: Discussionmentioning
confidence: 99%